2D gravity qualitative modeling to identify bedrock and volcanic rocks in South Lampung region - Zaenudin, Ahmad; Darmawan, I Gede Boy; Laimeheriwa, George (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
Gravity measurement has been conducted in South Lampung area to study the characteristics of the distribution of bedrock and igneous rocks, especially those that can be utilized for development in the National Strategic Area of the Sunda Strait. This study uses a 2D qualitative modeling method and utilizing spectrum analysis of complete Bouguer anomaly data. Based on the result of modeling of residual gravity anomaly, it was found that the intrusion pattern on Sulan granitoid pluton and surrounding plutons showed a significant intrusion of the body and scattered in some Tarahan area. 2D qualitative modeling shows Paleozoic metamorphic rocks are responsible as bedding rocks, and the spread was identified scattered throughout the study area, although it cannot be ascertained whether the bedrock in the Bakauheni area is precisely the same rock as the bedrock in Tarahan area. Meanwhile, Quaternary volcanic rocks are still dominated by tuffaceous sandstone and breccia. This method also confirms that andesite lava is commonly found as a product of the eruption of Mount Rajabasa and Pre-Rajabasa in the Bakauheni region. Nevertheless, some potential of basaltic andesite rocks can be obtained in monogenetic volcanic zones exposed around the foot of Mount Rajabasa.